Iqhiya: turbantes e tecidos conectando mulheres negras: Brasil, África do Sul e Moçambique - Silva, Rosyane Maria da (2020)
This study analyzed the meanings and symbologies that black Brazilian and African women establish for the use of Turbans (Iqhiya, Turban, Headwrap, Doek, Ojá) in their lives in the cities of Cape Town (South Africa), Maputo (Mozambique), Franca, São Paulo and Salvador (Brazil). This research sought to discover historical and cultural meanings in the use of Turbans, as well as to investigate how their use represents a connection between these countries in the diaspora, which may influence the self-esteem, resistance, sense of belonging and empowerment of these women. In addition, we also aimed to demonstrate the differences in the use of the Turban and new ways of using and signifying it. To this end, we interviewed black African and Brazilian women, reinforcing the importance of orality and black memories. The analysis of the interviews allowed the identification of three master keys for the interpretation of the uses of Turbans: 1) Re-existences, 2) Identities and 3) Ongoing transits: Africa and diasporas. Equally, offspring carrying has become a key element to pack and sew these continental wefts, as in addition to building cultural identification, strengthening the mother's identity and creating a maternal bond, it rescues the ancestral way of carrying, highlighting the importance of cultural maintenance and reexistence of black population. Based on these cultural expressions, we associate this relationship with the fabric itself - admittedly necessary - both for Turbantar (the act of wearing Turbans) and for carrying offspring –, especially with the Capulanas, since they take us directly to Mozambique, and are, literally, a cloth that tells the stories of a people. The analysis of the use of Turbans, Capulanas and carrying demonstrated that these identity components have a greater number of similarities than differences in the contexts in question. It is noteworthy that despite the long period elapsed from the experiences of enslavement and the Atlantic distances between the countries, we found similar models, ways of tying and uses of the Turbans as well as carrying, which established connections in terms of aesthetics and culture, in addition to crowning black women here and there. We conclude that for these women, ancestral connections were maintained based on such an imposing and diverse outfit, which full of stories, ancestry, identities and cultures. Turbantar and carrying are evidently linked to the memories of corporeality, beauty, resistance, blackness, identities and reconnection to the ancestry of black women